A análise da pedagogia de Makarenko por Lukács e a relação entre o processo educativo e o de desenvolvimento histórico-social do ser humano: contribuições à psicologia sócio-histórica - Alfredo, Raquel Antonio (2013)
This research has its origin in the text "The Socialist Construction and the Birth of the New Man - Makarenko: The path to Life" written in 1951 and taken from a German compilation of the work of G. Lukacs (1971), especifically, volume II of a subset of three volumes, which is entitled "Problems of Realism." In this research, this text of Lukács is proposed as a reference in the analysis of educational problems, considering that in it like in his "The Ontology of Social Being" (2004, p.75), the Hungarian philosopher offers the possibility to conclude that the proposition that the tool as the most important key in understanding those steps in the human evolution over which we detain no other documents. Saying it in a more specific way: it is argued that from the analysis of the Pedagogy of Makarenko made by Lukács, we can deduce the proposition of "The Pedagogical Poem" as objectification, meaning the tools that tell us much more about the life of the men who handled them, than that it appears to be in them at first sight, and that the The Pedagogical Poem not only reveals the evolutionary history in itself, but also opens broad perspectives on lifestyles including a vision of the world, etc., from the [Gorki colonists]. Thus, with the help of the fundamental assumptions of historical dialetical materialism, the aim being to make the theoretical methodological elements explicit, that mediated the referred analysis of Lukács, consolidating it as a source of theorizing about the dialectical relationship between the process of the social-historic development of the human being and the educational process, like a key for understanding of the possibilities wich slumber in socialist pedagogy. For this reason, we submit the thesis by which Lukacs argues "The Pedagogical Poem" by Makarenko for analysis, as an elaboration which contains sufficient theoretical methodological elements for its assertion that work relates to the pre-history of the socialist pedagogy like "Primitive Accumulation" does to this educational perspective. Beyond this, considering the fact that the historical-dialectical materialism was constituted as a common theoretical essential part of the production of the principal authors of this study, we analysed possible theoretical approaches between the production of Makarenko (1934, 1989), Lukacs (1951, 1971) and Vygotsky (1996). Initially we established the translation and definition of this analytical text of Lukacs as the main bibliographic source, based on which we consolidated the theoretical-methodological analysis of the relationship between the educational process and the socio-historical development of the human being, by means of a joint analysis of the pedagogy of Makarenko by Lukacs with the theoretical-methodological assertions of socio-historical psychology, whose main reference constitute the legacy of L.S.Vygotsky (1896-1934), and A.N.Leontiev (1903-1978) and A.R.Luria (1902-1977). With the aim of broadening and deepening the theoretical debate, we mainly used the contribution of Jovine (1977), Heller (1972) and Frederico (2005), Bock (1999) and Duarte (1993). By means of this research we came the concclusion that the study of text G. Lukács on Makarenko s experience provides an enlargement of the field of research in Educational Psychology and also in the analysis of possible theoretical approaches between the method of materialized analysis in the work of the Hungarian philosopher and that one defended by the so-called School of Vygotsky and consequently with the theoretical fundamentals defended by the socio-historical psychology